Step-cut osteotomy in neglected Monteggia fracture dislocation in pediatric and adolescent patients: A retrospective study - Chetan Peshin; Rohan Ratra; Anil Kumar Juyal (Journal of Orthopaedic Surgery, 2020)
Introduction: Neglected Monteggia fracture dislocation in children leads to significant restriction of daily activities by causing decreased range of motion at elbow, stiffness, deformity, and neurological compromise. Various treatment strategies have been described in the literature and one of them is ulnar osteotomy combined with reduction of radial head and annular ligament reconstruction. Aim: The aim of this study was to evaluate the results of step-cut osteotomy without the use of bone grafting with reconstruction of annular ligament in the management of neglected Monteggia fracture dislocation in children. Materials and Methods: A retrospective study was conducted in six patients with neglected Monteggia fracture dislocation with a mean age of 8.83 years. The median interval between the original injury and the corrective surgery for 6 patients was 4.4 months (range 1–12 months). All children underwent step-cut osteotomy of ulna, open reduction of radial head, and annular ligament reconstruction. Mayo Elbow Performance Index (MEPI) score was used for evaluation. Results: The ulnar osteotomies healed uneventfully without the need for a bone graft. Elbow range of motion improved post-op along with improved elbow functioning as indicated by raised MEPI score. The MEPI score was excellent in 5 cases and fair in 1 case. Conclusion: Step-cut osteotomy alone without the use of bone grafting and reinforcement with annular ligament repair is a simple yet effective technique for treating neglected Monteggia fracture dislocation.